New and Old Mechanisms Associated with Hypertension in the Elderly - Petra J. Mateos-Cáceres; Jose J. Zamorano-León; Pablo Rodríguez-Sierra; Carlos Macaya; Antonio J. López-Farré (International Journal of Hypertension)
Hypertension is a widely prevalent and important risk factor for cardiovascular diseases that increase with aging. The hallmark of hypertension in the elderly is increased vascular dysfunction. However, the molecular mechanisms by which increased blood pressure leads to vascular injury and impaired endothelial function are not well defined. In the present paper, we will analyze several mechanisms described in the scientific literature involved in hypertension in the elderly as endothelial dysfunction, increased oxygen delivery to tissues, inflammation, cellular apoptosis, and increased concentration of active metabolites. Also, we will focus on new molecular mechanisms involved in hypertension such as telomeres shortening, progenitor cells, circulating microparticles, and epigenetic factors that have appeared as possible causes of hypertension in the elderly. These molecular mechanisms may elucidate different origin for hypertension in the elderly and provide us with new targets for hypertension treatment.